Pelatihan Pembuatan Media Pembelajaran Bagi Guru Berbasis ICT dan VSDC Di MIS Al Abrar Kota Makassar - Abd. Rahim Mansyur (Education and Learning Journal, 2023)
This study used the lecture method and questions and answers were given to convey the material to be given to partner MI teachers. 1) The lecture method aims to convey a series of theories and procedures for making literary teaching materials, and how the learning process can be carried out properly and effectively through Microteaching, 2) The discussion and question and answer method is used to make it easier for instructors or executors to determine strategies to be applied in mentoring. While the debriefing is conducted to check whether the participants have understood the ICT-based learning material provided by the instructor, besides that the question and answer session helps participants adapt the media to the subject to be taught. The assignment method is used to train teachers to make ICT-based learning media using VSDC and PPT and implement these media to students. 3) Practice and assignment methods are used to provide training to workshop participants to prepare and compile ICT-based learning media using VSDC and PPT. 4) The process of making ICT-based learning media is preparing a laptop or PC complete with an Internet network, then preparing a guidebook that can be used by teachers in running applications for making ICT-based media using VSDC and PPT. The first problem encountered in learning literature is 1) the teacher's inability to master literature, 2) the lack of teaching skills for teachers, 3) the lack of understanding of literature. Furthermore, the second problem in the field of technology is 1) not being able to package media properly, 2) have never attended training in making teaching media, 3) lack of motivation in improving IT skills. Given the problems mentioned above, the solutions offered are 1) training in making teaching materials for literature, 2) training for making learning media 3) training and mentoring for packaging literary learning media, 4) training and strengthening strategies in using media that have been made by the teacher , 5) Training on promoting works through websites/youtube. Through this media the teacher will be helped to explain how to read poetry properly according to what is shown by the audio-visual media. School is a place for seeking knowledge, but if the school is not able to make children excited, it is necessary to re- evaluate what is lacking in the learning process. While those who are assessed are still at the level of memorization ability. Therefore, this service is carried out to help solve problems that occur in learning in Madrasas.